Protestáns konfessziók együttélése – szövetségek, uniók mint egzisztenciális stratégia - KÓNYA, Annamária (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The Coexistence of Protestant Confessions – Alliances, Unions as an Existential Strategy It is generally known that during the Reformation, there was no good relationship between the Protestant denominations, and rather discord and intolerance characterized the relationship between the Lutheran and Calvinist churches in particular. The same applied to the rejectionist and sometimes-persecutory attitude of the two leading Protestant doctrines towards radical tendencies. This was manifested on several levels and for different reasons. First and foremost, it was caused by theological differences, i.e. each Reformation doctrine was convinced of the sole truth of its own doctrine. These disagreements were manifested in the first joint Protestant synods and later in disputes between individual theologians, in polemical writings, but also in the denial of any unification of religions. Another important factor that influenced the bad relationship was, of course, the loss of believers. Especially the Evangelical Church, which had been established in the mid-16th century, feared that the later spreading Swiss Reformation doctrines would cause a loss of believers. However, there have been individual, local examples where different Protestant religions have been able to cooperate and ally with each other very well and profitably when mutual benefit or even existential motivation was at stake. The paper would like to outline some examples of this: the union between the Protestants and the Reformed in Zemplín County existing throughout six decades in the 17th century, the union between the Reformed Church and the Bohemian brethren concluded in 1647, and the union in the form of smooth coexistence between the Protestants and the Reformed in Košice in the first half of the 17th century.